PEMBERIAN PELATIHAN ( PEMBUATAN PROPOSAL, VARIAN PRODUK, PENGEMASAN PRODUK, PEMASARAN DIGITAL, PEMBUKUAN DAN PEMBUATAN LAPORAN KEUANGAN SEDERHANA) TERHADAP PARA PELAKU UMKM PENGOLAHAN IKAN ASIN DI DESA KUBANG PUJI KABUPATEN SERANG BANTEN - Romli, Ombi; Zahroh, Hanifah Rifda (Batara Wisnu : Indonesian Journal of Community Services, 2021)
The obligation as a lecturer in carrying out tri dharma is one of them through community service. This community service aims to increase the ability and skills of salted fish processing businesses and is strived to switch from conventional to modern industry immediately. Based on our analysis as a devotional team, the devotion in this period was held from July 14 to August 15, 2021, spending approximately 34 (thirty-four) days, and was located in kubang Puji village of Pontang District of Serang Banten Regency. The number of participants is approximately 20 (twenty) participants, 70% of business people, and some surrounding residents. The first day of training is: making proposals, the second day of product variant training, the third day of product packaging training, the fourth day of digital marketing training, the fifth day of bookkeeping training, and the creation of simple financial statements. The methods applied in these training are through lectures or presentations of materials, demonstrations, practice exercises, and discussions with participants. After the training activity is completed, the training committee will conduct a survey and evaluation to see how much impact the change will have on the salt fish processing MSME business actors. The training results showed that the training in this community service program was efficient and on target, all evidenced by the survey results a week after the training. It turned out that many participants immediately practiced it. Through this training, various skills are expected to be able to encourage increasing skills, including being able to make proposals, product variants, product packaging, product marketing using social media, business bookkeeping, and making simple financial statements to MSME actors processing salted fish in Kubang Village Puji Pontang Kabuputen Serang Banten District. These training are also expected to increase the income of business actors to prosper all parties, especially business actors and employees. They have a positive impact can also develop local government revenues that will impact the equalization of regional development. All the obstacles that arise in each training can be overcome through two-way communication, and build each other, so that event after the event can run well according to this plan, all thanks to the cooperation of all parties. As for the criticism and advice that can be submitted from the results of community service programs, participants are expected to continue to have the spirit and motivation to develop their business through the training given. For academics can always transfer knowledge to all those who need it and